REQUIREMENTS OF CARBOHYDRATES, PROTEINS, FATS, PHYSICAL ACTIVITY, AND THE MENSTRUAL CYCLE OF ADOLESCENTS IN SURABAYA - Victorya; Yanuar Dini, Cleonara (JURNAL KESMAS DAN GIZI (JKG), 2023)
The menstrual cycle is a crucial thing for women. Irregular menstrual cycles can interfere their mental, physical, and even social lives. Disorders of the menstrual cycle are closely related to several factors, including intake of macronutrients and physical activity. The purpose of this study was to determine the correlation between levels of consumption of macronutrients and physical activity with the menstrual cycle. It was a cross-sectional study with 75 female students of the Nutrition Departement at State University of Surabaya who were taken with non-probability sampling. SQ-FFQ were used to estimate dietary intake of macronutrient, physical activity level were measured by using IPAQ-SF questionnaire, and menstrual cycle data were recorded using the menstrual cycle form using the self-record method. The correlation test between the level of consumption of macronutrients and physical activity with the menstrual cycle are using the Spearman test. The level of consumption of carbohydrates and fats in the majority of respondents respectively 41.3% and 44% according to the daily needs of the respondents. The level of physical activity of the majority of respondents in the moderate category was 58.7%. A total of 52 respondents (69.3%) experienced normal menstrual cycles and this was significantly related to carbohydrate intake (p=0.001; r=0,4), fat intake (p=0.001; r=0,4), and physical activity (p=0.005; r=0,4). Meanwhile, 50.7% of respondents with a high level of protein consumption did not have a significant relationship with the menstrual cycle (p=0.289; -0,1). It was concluded that there was a significant relation between the level of consumption of carbohydrates, fats, and physical activity with the menstrual cycle. Conversely there is no correlation between the level of protein consumption and the menstrual cycle.